Prevention of criminal victimization: An Islamic approach - Zawawi, Majdah; Hussin, Nasimah (INSI Publications, 2012)
Living and working in a safe area gives every person a confident feeling. It enhances productivity and ensures a safe community. In order to achieve it, crime prevention measures are always considered the main agenda of public authorities. Nevertheless, it has usually been overlooked that the victim him/herself can be the contributing factor to the criminal incident. The objective of this paper is to provide suggestions as to how these questions could be answered. The key to these problems lies in educating the community on the preventive measures that could be taken in order to avoid victimization of individuals. Such suggestions are based on Shari‘ah principles. This is done through an analysis of the rulings of the Qur’an and hadith of the Prophet s.a.w. Hence, this paper discusses the preventive measures that can be observed by both individuals and the community to prevent criminal victimization.